Labelisasi Halal dan Strategi Pemasaran Kopi Robusta pada Masyarakat Desa Talang Jawa Kecamatan Tebing Tinggi Kabupaten Empat Lawang Sum-Sel - Salim, Amir; Lubis, Rusdi Hamka; Purnamasari, Anggun; Utami, Dian Tri (Prodi Ekonomi Syariah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2021)
This study examines the Inclusion of Halal Labels and Marketing Strategies on the Purchase of Robusta Coffee in the Talang Jawa Village Community, Kec. High Cliff Kab. Four Laws. This type of research is a field research (filed research). This research aims to obtain information about Halal Labels and Marketing Strategies for the Purchase of Robusta Coffee in the Talang Jawa Village Community, Kec. High Cliff Kab. Four Lawangs that plunge directly into an object. This research is a field research that uses qualitative methods where a case study approach is carried out, then a data collection method used is observation, interviews, and documentation. Based on the results of the research obtained, the authors conclude that the effect of Halal labeling is very influential on consumer purchasing decisions, because after obtaining permission and certification of halal labeling consumers are sure of the quality of the coffee product.